2014
DOI: 10.1120/jacmp.v15i3.4641
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric benefits of IMRT and VMAT in the treatment of middle thoracic esophageal cancer: is the conformal radiotherapy still an alternative option?

Abstract: The purpose of this study is to investigate the dosimetric differences among conformal radiotherapy (CRT), intensity‐modulated radiotherapy (IMRT), and volumetric‐modulated radiotherapy (VMAT) in the treatment of middle thoracic esophageal cancer, and determine the most appropriate treatment modality. IMRT and one‐arc VMAT plans were generated for eight middle thoracic esophageal cancer patients treated previous with CRT. The planning target volume (PTV) coverage and protections on organs at risk of three plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
2
28
0
1
Order By: Relevance
“…The unique dosimetric properties of IMRT and VMAT have the potential to reduce the injury to uninvolved structures while attaining appropriate tumor coverage and may lead to an improved therapeutic index with respect to tumor control and toxicity [1517]. Particularly, VMAT technique had gained enormous interest world-wide by using continuous changing MLC movement, gantry rotation and dose rate with less MUs and delivery time [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…The unique dosimetric properties of IMRT and VMAT have the potential to reduce the injury to uninvolved structures while attaining appropriate tumor coverage and may lead to an improved therapeutic index with respect to tumor control and toxicity [1517]. Particularly, VMAT technique had gained enormous interest world-wide by using continuous changing MLC movement, gantry rotation and dose rate with less MUs and delivery time [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…IMRT beem plans to 3DCRT in lower oesophageal cancer patients and they reported a 5% reduction in lung V20 with IMRT plans which is different than our findings. Similarly, Wu et al [13] reported a lower lung V20 with IMRT yet not reaching a statistically significant value. Nutting et al [19] reported a reduction in mean lung dose upon using a 4 field IMRT when compared to the 9 fields IMRT and the 3DCRT plans.…”
Section: Discussionmentioning
confidence: 88%
“…Current study didn't show any significant improvement in the PTV coverage by IMRT compared to 3DCRT and this finding matches the results from the study published by Ghosh et al [12] where the dose homogeneity was comparable for both 3DCRT and IMRT techniques. Similarly the study by Wu et al [13] reported no significant superiority of IMRT or even Volumetric Modulated Arc Therapy (VMAT) plans over 3DCRT in middle oesophageal cancer cases. Our findings differ from the results of the study by Fenkell et al [5]; where they compared IMRT with 3DCRT in the treatment of the cervical esophageal cancer, the median coverage of various PTVs even 50 and 70 were all improved with…”
Section: Discussionmentioning
confidence: 93%
“…Most of the time, the difficulty is to limit the irradiated volume or the total dose so as not to compromise the benefit/risk ratio. In this context, Intensity-Modulated Radiotherapy (IMRT) [23] or Volumetric Modulated Arctherapy (VMAT) [24] could be used to increase mediastinal irradiated volumes or dose escalation to the primary tumor while effectively protecting healthy tissues. In the MD Anderson Cancer Center retrospective experience, in 676 patients with esophageal cancer treated by exclusive CRT (of whom 263 were treated by IMRT), the authors showed that loco-regional control and overall survival were significantly better for IMRT than for three-dimensional radiotherapy [25].…”
Section: Discussionmentioning
confidence: 99%